1998
DOI: 10.1074/jbc.273.10.5478
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Peripheral-type Benzodiazepine Receptor Antisense Knockout on MA-10 Leydig Cell Proliferation and Steroidogenesis

Abstract: The peripheral-type benzodiazepine receptor (PBR) is not only widely expressed throughout the body, but it is also genetically conserved from bacteria to humans. Many functions have been attributed to it, but its primary role remains a puzzle. In the current study, we stably transfected cultures of MA-10 Leydig cells with either control or 18-kDa PBR antisense knockout plasmids. The antisense knockout vector was driven by the human enkephalin promoter, which contains two cAMP response elements, such that cAMP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
51
1
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 34 publications
4
51
1
2
Order By: Relevance
“…Answer: The aforementioned study on TSPO knockdown in MA-10 Leydig cells did not observe differences in acute production of PROG (Kelly-Hershkovitz et al 1998). They observed that in TSPO antisense 'knockout' cells, PROG levels decreased by about 20% and only at a late time point (24 h), leading to an interpretation that TSPO may play a role in PROG metabolism rather than synthesis (Kelly-Hershkovitz et al 1998).…”
Section: Tspo Knockdown In Cellsmentioning
confidence: 99%
See 3 more Smart Citations
“…Answer: The aforementioned study on TSPO knockdown in MA-10 Leydig cells did not observe differences in acute production of PROG (Kelly-Hershkovitz et al 1998). They observed that in TSPO antisense 'knockout' cells, PROG levels decreased by about 20% and only at a late time point (24 h), leading to an interpretation that TSPO may play a role in PROG metabolism rather than synthesis (Kelly-Hershkovitz et al 1998).…”
Section: Tspo Knockdown In Cellsmentioning
confidence: 99%
“…They observed that in TSPO antisense 'knockout' cells, PROG levels decreased by about 20% and only at a late time point (24 h), leading to an interpretation that TSPO may play a role in PROG metabolism rather than synthesis (Kelly-Hershkovitz et al 1998). They concluded that 'further studies are needed to confirm the involvement of the 18-kDa PBR subunit in MA-10 Leydig cell steroid biosynthesis' (Kelly-Hershkovitz et al 1998).…”
Section: Tspo Knockdown In Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…While it was believed initially that transmembrane cholesterol transfer could be facilitated during the importation of StAR mediated by its N-terminal addressing sequence, the subsequent discovery that all the mutations that inactivate StAR are located at its C-terminal end (61) and that the biologically active domain of StAR resides in its C-terminus (68), strongly suggested that additional components(s) participate in StAR action. The peripheral-type benzodiazepine receptor has been proposed as one such partner (69,70).…”
Section: The Role Of Star In the Acute Regulation Of Steroidogenesismentioning
confidence: 99%